2020
DOI: 10.3390/app10155201
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance of Cultured Meat: An Updated Review (2018–2020)

Abstract: Cultured meat is one of a number of alternative proteins which can help to reduce the demand for meat from animals in the future. As cultured meat nears commercialization, research on consumers’ perceptions of the technology has proliferated. We build on our 2018 systematic review to identify 26 empirical studies on consumer acceptance of cultured meat published in peer-reviewed journals since then. We find support for many of the findings of our previous review, as well as novel insights into the market for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
130
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(191 citation statements)
references
References 55 publications
14
130
2
3
Order By: Relevance
“…Stephen et al ( 2018 ) emphasize the diversity of responses within and across studies. Here, we mostly rely on the meta-analyses conducted by Bryant and Barnett ( 2018 , 2020 ). They report that the proportion of participants willing to try cultured meat varies significantly, from 5 to 11% in Hocquette et al ( 2015 ) and up to 65% in Wilks and Philips ( 2017 ).…”
Section: Some Demand Side Issuesmentioning
confidence: 99%
“…Stephen et al ( 2018 ) emphasize the diversity of responses within and across studies. Here, we mostly rely on the meta-analyses conducted by Bryant and Barnett ( 2018 , 2020 ). They report that the proportion of participants willing to try cultured meat varies significantly, from 5 to 11% in Hocquette et al ( 2015 ) and up to 65% in Wilks and Philips ( 2017 ).…”
Section: Some Demand Side Issuesmentioning
confidence: 99%
“…A number of studies have identified that familiarity with cell-culture technology is a positive predictor of cultivated meat acceptance [ 22 , 23 , 24 ]. A science communication approach was recently developed for describing the process of producing meat through cellular agriculture in a familiar manner, called ‘meat cultivation’ [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on consumer acceptance of cultivated meat has proliferated in recent years [ 22 ] and has identified a consistent set of motivators and barriers among consumers. Although consumers generally recognize the benefits of cultivated meat for animals and the environment, many raise taste, price, and safety concerns [ 21 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of 3D bioprinting of cultured meat are multiple, such as precise regulation of protein, fat, and other nutritional content [ 150 ], speed of production, ability to produce relevant forms i.e., steak-like form which can lead to greater consumer acceptance [ 151 ], and adaptation for use in extreme conditions such as space [ 152 ]. The world’s first cultivated ribeye steak has been 3D bioprinted by the Israeli company Aleph farms in February 2021 [ 153 ].…”
Section: Bioreactors and Scaffoldingmentioning
confidence: 99%